Frequency Regulation by Electric Vehicle during Grid Restoration using Adaptive Optimal Control. Issue 4 (2019) - Nayak, Abhishek; Rana, Rubi; Mishra, Sukumar
Abstract: The restoration process of power system after a blackout involves generation restart, energization of buses/power lines and sequential load pickup. In the process of doing so, system frequency tends to deviate from its nominal value and should be checked within the tolerance range. Electric vehicles (EVs) with bidirectional power flow capabilities can act as fast response compensator during the generation-load imbalance while ongoing restoration process. The system dynamics is associated with system parameters which are often not known. To this end, an adaptive optimal controller has been formulated to provide the EV an optimal charging/discharging solution at the behest of no system information available at controller end. Simulation results confirm the regulation of system frequency by control action obtained through EV charging/discharging.